A review on the generation of solid wastes and their utilization in Indian steel industries. (3rd April 2017) - Sharma, Neelam; Nurni, Viswanathan N.; Tathavadkar, Vilas; Basu, Somnath
ABSTRACT: More and more primary metal production and processing units are being shifted away from the developed countries to the developing countries. India is poised to become one of the largest producers of metals after China. This poses its own challenges in terms of solid waste management. As far as the production of primary metals are concerned, steel industries produce the largest amount of solid wastes. India has rich deposits of haematite. Because of high alumina content and inferior coke quality, approximately 1.6 tons of solid wastes are generated per ton of the steel produced. Most of the Blast Furnace slag is granulated and is used for manufacturing cement. However, steel making slag that contains high amounts of Fe poses challenges. This paper discusses the issues pertaining to solid waste generation from iron and steel making processes in terms of volumes, challenges and efforts towards recycling and utilization.